Studies Islamic Culture On Time Update - Febby Adinda; Haidar Putra Daulay; Sholihah Titin Sumanti (Sean Institute, 2025)
The purpose of writing this paper is to find out the state of Islam during the renewal period. Islamic renewal is an effort to adapt Islamic religious knowledge to all developments that occur along with the challenges of the times. There is a reason for the progress of science, technology and modern civilization. In this case, renewal does not mean that Islam was born for the second time or that there were changes, reductions, or additions to the revelation of the Qur'an. However, what happened was only an adjustment to the interpretation of the verses of the Qur'an against the basic teachings of religion to suit what is needed people at that time.